Inspections and Testing in Overhead Transmission Line (OHL) Civil Works as a Part of Quality Control and Quality Assurance - Narayanasamy, MahendraKumar; Govindarajulu, Sudharsanan (International Journal of Scientific Research in Civil Engineering, 2023)
Quality control and quality assurance play a vital role in the successful execution of overhead transmission line (OHL) civil works. Inspections and testing are a part of quality control and quality assurance in OHL civil works. OHL projects can ensure the delivery of high-quality infrastructure that meets safety, reliability, and performance requirements. Implementing testing and inspections throughout the construction process will contribute to efficient transmission of power, benefiting all stakeholders.
Keywords: Inspections; testing; OHL; QC&QA